Entrepreneurial Orientation and Internationalization of SME’s: A Scoping Review - Hamdana Hamdana; Danardana Murwani; Imam Mukhlis (Eduvest - Journal of Universal Studies, 2022)
The purpose of this scoping review is to verify the evidence that is already available regarding the entrepreneurial orientation and internationalization of SMEs. Researchers used the model from Arskey and O'Malley to perform the scoping review method and the PRISMA flowchart to identify the literature found. Researchers found 13 relevant articles related to entrepreneurial orientation and the internationalization of SMEs. Risk-taking, inventiveness, and proactiveness are all important components of an entrepreneurial mindset, and they are all important contributors to effective internationalization. This shows that an entrepreneurial orientation is needed by SMEs to move towards internationalization.